Hubungan Kebiasaan Konsumsi Makanan Siap Saji (Fast Food) dengan Status Gizi pada Remaja - Patarru', Fitriyanti; Situngkir, Rosmina; Heumasse, Chindy F; Ahudara, Chrily Graselya S (Jurnal Penelitian Kesehatan SUARA FORIKES, 2022)
Background: The habit of consuming fast food in adolescents is influenced by changes in lifestyle and eating patterns that are not good if, excessive consumption will cause nutritional problems in adolescents, such as obesity or overweight. Objective: to determine the relationship betweenconsumption habits fast food and nutritional status in adolescents. Method: This type of study analytic observational with a cross sectional study design. The sampling technique used was accidental sampling with a total of 84 respondents. The research instrument for measuringconsumption habits fast food used a food frequency questionnaire (FFQ) and for measuring nutritional status using a BB scale (Bathroom Scale) and a meter (microtoise). Results: The results of the study used the Chi-Square test with a significance level, Ï = 0.000